Complications of Aesthetic and Reconstructive Breast Implant Capsulectomy: An Analysis of 7486 Patients Using Nationwide Outcomes Data - Xu, Hong Hao; Abi-Rafeh, Jad; Davison, Peter; Winocour, Sebastian; Matros, Evan; Vorstenbosch, Joshua (Aesthetic surgery journal, 2024)
Abstract Background Despite increasing demand for breast capsular surgery to treat various benign and malignant implant-related pathologies, high-quality evidence elucidating complication profiles of capsulectomy and capsulotomy is lacking. Objectives The aim of this study was to provide the largest-scale analysis of associated outcomes and complications using the Tracking Operations and Outcomes for Plastic Surgeons (TOPS) database, and to investigate clinical scenarios that may subject patients to increased risks for complications, most notably extent of capsular surgery (complete vs partial) and index indication of implantation (aesthetic vs reconstructive). Methods An analysis of the TOPS database from 2008 to 2019 was performed. CPT codes were used to identify complete capsulectomy and partial capsulectomy/capsulotomy cases. Breast implant exchange procedures constituted procedural controls. Results In total, 7486 patients (10,703 breasts) undergoing capsulectomy or capsulotomy were assessed. Relative to controls, capsulectomy (4.40% vs 5.79%), but not capsulotomy (4.40% vs 4.50%), demonstrated higher overall complication rates. Both capsulectomies (0.83% vs 0.23%) and capsulotomies (0.56% vs 0.23%) also had greater rates of seroma relative to controls. Subgroup analyses demonstrated that reconstructive patients, relative to aesthetic patients, experienced greater overall complications (6.76% vs 4.34%), and increased risks for seroma (1.06% vs 0.47%), dehiscence (0.46% vs 0.14%), surgical site infections (1.03% vs 0.23%), and implant loss (0.52% vs 0.23%). A detailed synthesis of 30-day outcomes, including all patient- and breast-specific complications, for both capsulectomy and capsulotomy, stratified according to all potential confounders, is presented herein. Conclusions Surgeries on the breast capsule are safe overall, although complete capsulectomies and reconstructive patients are associated with significantly increased operative risks. The present findings will enhance patient selection, counseling, and informed consent. Level of Evidence: 3